Fungos derivados da Antártica: biodiversidade e produção de enzimas lignocelulóticas a baixas e médias temperaturas - Barato, Mariana Blanco [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The interest in microorganisms, especially fungi derived from underexplored environments such as Antarctica has increased in recent decades. Antarctica ecosystems have characteristics of extreme temperature, salinity or pH which prevents the development of many forms of life, being the micro-organisms the best adapted to proliferate in substrates of this continent. Microorganisms that grow in Antarctic ecosystems are able to produce cold adapted enzymes, which have potential application in many sectors of economic importance. This project is associated with the FAPESP Project 2010/17033-0 entitled “Biotechnological Exploitation of fungi derived from Antarctica, coordinated by Prof. Dr. Lara Sette and aims to know the biodiversity, to select filamentous fungi with lignocellulolytic potential and to evaluate the production of these enzymes at low and medium temperatures. For this purpose, we used 160 isolates recovered from marine and terrestrial samples of the Antarctic continent that have been maintained in the research collection of DRM (CPQBA/UNICAMP) and in the Microbial Resource Center of UNESP (CRM-UNESP). After the first screening (on solid medium and in liquid medium), two fungi were selected for subsequent experiments, one from marine sample (P1) and another one from terrestrial sample (M7), which were identified as Cadophora luteo-olivacea and Cadophora malorum, respectively. The assays regarding the evaluation of different factors in the production of ligninases allowed the identification of the effects of each variable on the enzyme activity. However, the optimization of laccase production by Cadophora luteo olivacea P1 was not efficient because the low activity of this enzyme under the conditions studied. In lignocellulosic substrates the fungus C. malorum M7 presents the best xylanase activity when grown on sugarcane bagasse and corn cobs. Among the 160 filamentous fungi studied, 76 were taxonomically characterized...

O interesse por micro-organismos, em especial os fungos derivados de ambientes poucos explorados como a Antártica, tem crescido nas últimas décadas. Os ecossistemas da Antártica por serem caracterizados por extremos de temperatura, salinidade ou valores de pH, inviabilizam o desenvolvimento de muitas formas de vida, sendo os micro-organismos os mais adaptados para se proliferar nos substratos deste continente. Os micro-organismos que se desenvolvem nos ecossistemas Antárticos são capazes de produzir enzimas adaptadas ao frio, as quais possuem potencial aplicação em diversos setores de importância econômica. O presente projeto é parte do Projeto Fapesp 2010/17033-0 intitulado “Exploração biotecnológica de fungos derivados da Antártica” coordenado pela Profa. Dra. Lara Sette e teve como objetivo conhecer a biodiversidade, selecionar fungos filamentosos com potencial ligninocelulolítico e avaliar a produção dessas enzimas a médias e baixas temperaturas. Para tanto, foram utilizados 160 isolados recuperados de amostras marinhas e terrestres do continente Antártico que se encontram mantidos na coleção de pesquisa da DRM (CPQBA/UNICAMP) e na Central de Recursos Microbianos da UNESP (CRM-UNESP). Após a triagem inicial (em meio sólido e em meio líquido) dois fungos ligninolíticos foram selecionados para os experimentos subsequentes, um de origem marinha (P1) e outro de origem terrestre (M7), os quais foram identificados como Cadophora luteo-olivacea e Cadophora malorum, respectivamente. Os ensaios referentes à avaliação de diferentes fatores na produção de ligninases permitiu identificar os efeitos de cada uma das variáveis na atividade enzimática. Entretanto, a otimização da produção de lacase para o fungo C. luteo-olivacea P1 não foi eficiente, tendo em vista a baixa atividade desta enzima nas condições estudadas. Em substratos lignocelulósicos o fungo C. malorum M7 se destacou frente à atividade de...
Keywords: Fungi; Fungos; Enzimas; Biodiversidade; Enzimas - Biotecnologia; Baixas temperaturas; Fungos filamentosos - Antártida